2018
DOI: 10.1097/md.0000000000013349
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variants of dorsal scapular nerve in relation to the middle scalene muscle in Japanese population

Abstract: Dorsal scapular nerve (DSN) block is often performed in Japanese pain clinics to treat neck pain and katakori (a unique symptom in Japanese population characterized by myofascial pain syndromes such as shoulder girdle pain). However, to the best of our knowledge, there are only a few studies regarding anatomical variations in DSN paths around the middle scalene muscle (MSM) in Japanese population. Thus, we conducted a cadaveric study to examine anatomical variations in DSN paths around the MSM in Japanese popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…We attribute this interstudy discrepancy to natural anatomical variability coupled with the small sample sizes (n=18 and n=13 specimens). However, we cannot rule out ethnic differences in neural topography13 since our population consisted exclusively of a South East Asian sample whereas Short et al ,5 who carried out their investigation in Toronto (Canada), presumably included more Caucasian subjects. However, irrespective of the relative contributions of high versus low articular branches, PENG blocks constitute a viable analgesic strategy for THA because they reliably anaesthetise all articular branches derived from the femoral nerve.…”
Section: Discussionmentioning
confidence: 97%
“…We attribute this interstudy discrepancy to natural anatomical variability coupled with the small sample sizes (n=18 and n=13 specimens). However, we cannot rule out ethnic differences in neural topography13 since our population consisted exclusively of a South East Asian sample whereas Short et al ,5 who carried out their investigation in Toronto (Canada), presumably included more Caucasian subjects. However, irrespective of the relative contributions of high versus low articular branches, PENG blocks constitute a viable analgesic strategy for THA because they reliably anaesthetise all articular branches derived from the femoral nerve.…”
Section: Discussionmentioning
confidence: 97%
“…One of the methods frequently used for the relief of symptoms of DSN neuropathy is nerve blocks (Saporito, 2013). It has been reported that during middle scalene muscle block, the DSN may be damaged if it travels anterior to the muscle, because it remains more superficial (Tetsu et al, 2018). It has also been stated that there is a risk of DSN injury in interscalene nerve blocks (Kim et al, 2016).…”
Section: The Relationship Between the Dsn And The Scalene Musclesmentioning
confidence: 99%
“…According to classical anatomy knowledge, the DSN pierces the middle scalene muscle after its formation and runs in the posteroinferior direction (Moore et al, 2018;Moses et al, 2013;Schuenke et al, 2014;Standring, 2016;Tubbs et al, 2015). However, in the literature, variations have also been reported in terms of its relationship with scalene muscles (Lee et al, 1992;Nguyen et al, 2016Nguyen et al, , 2017Tetsu et al, 2018;Williams & Smith, 2020).…”
mentioning
confidence: 99%